PENDEKATAN PSIKIATRI KOMUNITAS PADA ORANG DENGAN HIV DAN POPULASI KUNCI MELALUI YAYASAN INSET DI KOTA MATARAM, NUSA TENGGARA BARAT - Savitri Yuanita; Cokorda Bagus Jaya Lesmana; Ni Ketut Putri Ariani; Ida Aju Kusuma Wardani; Anak Ayu Sri Wahyuni; Himawan Afrian; I Komang Ana Mahardika (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT People living with HIV (PLHIV) and key populations are at high risk of mental health problems due to persistent stigma, discrimination, and psychosocial stress. Limited availability of community-based mental health services highlights the need to integrate a community psychiatry approach into HIV care. This community service program aimed to identify mental health issues among PLHIV, key populations, and HIV service providers, as well as to implement community-based mental health interventions through Yayasan INSET in Mataram City, West Nusa Tenggara. The program was conducted in June 2025 using a community psychiatry approach. Interventions included mental health screening of service providers using the Depression Anxiety Stress Scales-42 (DASS-42), self-care classes, basic counseling training for peer supporters, and mental health education and consultation integrated with Mobile Voluntary Counselling and Testing (VCT) services. The results showed that most service providers were in a normal psychological condition, with some experiencing symptoms ranging from mild to severe, and there was an improvement in mental health literacy, coping capacity, and psychosocial support skills following the intervention. The integration of mental health services with Mobile VCT also expanded service coverage and enhanced community acceptance. This approach proved effective in supporting the mental health of PLHIV, key populations, and HIV service personnel, and shows potential for replication in similar settings. ABSTRAK Orang dengan HIV (ODHIV) dan populasi kunci berisiko tinggi mengalami gangguan kesehatan mental akibat stigma, diskriminasi, dan tekanan psikososial yang berkelanjutan. Keterbatasan layanan kesehatan jiwa berbasis komunitas menegaskan perlunya integrasi pendekatan psikiatri komunitas dalam layanan HIV. Kegiatan pengabdian masyarakat ini bertujuan menggambarkan permasalahan kesehatan mental pada ODHIV, populasi kunci, dan petugas layanan HIV, serta pelaksanaan intervensi kesehatan jiwa berbasis komunitas melalui Yayasan INSET di Kota Mataram, Nusa Tenggara Barat. Kegiatan dilaksanakan pada Juni 2025 dengan pendekatan psikiatri komunitas. Intervensi meliputi skrining kesehatan mental petugas menggunakan Depression Anxiety Stress Scales-42 (DASS-42), kelas self-care, pelatihan konseling dasar bagi pendukung sebaya, serta edukasi dan konsultasi kesehatan jiwa yang terintegrasi dengan layanan Mobile Voluntary Counselling and Testing (VCT). Hasil menunjukkan sebagian besar petugas berada pada kondisi psikologis normal dengan variasi gejala dari ringan hingga berat, serta terjadi peningkatan literasi kesehatan mental, kapasitas coping, dan keterampilan dukungan psikososial setelah intervensi. Integrasi layanan kesehatan jiwa dengan Mobile VCT juga memperluas jangkauan layanan dan meningkatkan penerimaan komunitas. Pendekatan ini efektif dalam mendukung kesehatan mental ODHIV, populasi kunci, dan tenaga pendukung layanan HIV serta berpotensi direplikasi di wilayah dengan karakteristik serupa.